Belles-Lettres Reading Strategies in the Process of Foreign Language Teaching - A. S. Komarov (Vestnik MGIMO-Universiteta, 2015)
The article is devoted to some of the teaching strategies based on the peculiarities of belles-lettres text. The author of the article analyses the peculiarities of the belles-lettres text which exert influence on the process of teaching reading skills and thus should be taken into account by foreign language teachers in their work with this type of text. The author argues that teaching belles-lettres reading skills should be centered on the five-level communication process between writer and reader. The teacher's aim is to create or adjust a system of reading instruction within the five levels so that he/she could improve students' reading skills. In the article, it is stated that the process of teaching reading skills should be congruent with the process of interpersonal communication between writer and reader. The author outlines the content of the teacher's approach to the work with this type of text within the process of foreign language instruction. The author describes two approaches to teaching belles-lettres reading skills as well as shows the prospects for the subjective approach. He also states high productivity and effectiveness of the subjective approach in teaching foreign languages. The article shows the importance of involving students who specialize in sciences into the process of belles-lettres reading while studying a foreign language for specific purposes.